2019
DOI: 10.1200/jgo.2019.5.suppl.93
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1, open-label, multicenter study to assess the safety, tolerability, and immunogenicity of mRNA-4157 alone in subjects with resected solid tumors and in combination with pembrolizumab in subjects with unresectable solid tumors (Keynote-603).

Abstract: 93 Background: T-cell targeting of mutation-derived epitopes (neoantigens) has been demonstrated to drive anti-tumor responses. Immunizing patients against such neoantigens in combination with a checkpoint inhibitor (CPI) may elicit greater anti-tumor responses than CPI alone. Mutations are rarely shared between patients, thus requiring a personalized approach to vaccine design. Methods: This is an interim report of a phase I dose escalation study of mRNA-4157 given as monotherapy in patients with resected so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…So far, pre-clinical data has shown promising results in favor of using DC-targeting nanoparticle formulations for the induction of potent anti-tumor responses. While nanotechnology for directly targeting DCs for anti-cancer immunotherapy is mainly applied in in vivo and ex-vivo models, some clinical trials are conducted with this platform ( 106 , 191 ). Unfortunately, liposomes targeting the DC-SIGN receptor in patients with metastatic melanoma did not yield desired clinical results ( 106 ).…”
Section: Discussionmentioning
confidence: 99%
“…So far, pre-clinical data has shown promising results in favor of using DC-targeting nanoparticle formulations for the induction of potent anti-tumor responses. While nanotechnology for directly targeting DCs for anti-cancer immunotherapy is mainly applied in in vivo and ex-vivo models, some clinical trials are conducted with this platform ( 106 , 191 ). Unfortunately, liposomes targeting the DC-SIGN receptor in patients with metastatic melanoma did not yield desired clinical results ( 106 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the overall response rate (ORR) for the treatment of 10 cases of HPV-negative head and neck squamous cell carcinoma (HPV - HNSCC) with the mRNA-4157 vaccine was 50%, of which 2 cases achieved complete remission (CR). 355 – 358 …”
Section: Progress In Clinical Research On Mrna Vaccinesmentioning
confidence: 99%
“…Another Phase I trial involved administration of a lipid-coated mRNA-4157 that encodes for a wide range of tumour antigens to elicit tumour responses independently, as well as in combination with the anti-PD1 humanized antibody pembrolizumab. The initial study showed good dose tolerance paving way for Phase II trials for this combination [ 171 ]. Another Phase I trial had investigated the anticancer potential of a RNA-lipoplex for triggering dendritic cell maturation and T-cell response in a small cohort of patients with advanced melanoma.…”
Section: Nanoparticles With Immunotherapy In Clinical Trialsmentioning
confidence: 99%